Inteligencia emocional y clima institucional en la enseñanza remota, instituciones educativas del nivel inicial de la ciudad de Nauta 2022 - Perez Tello, Sara Alegria (2022)
The purpose of this study is to link emotional intelligence and institutional climate in distance education in basic education institutions in the city of Nauta in the year 2022. The study was correlational and used a cross-domain design. The population under study is 120 people, the youngest teachers of public educational institutions in the city of Nauta. For convenience, there were 40 teachers in his sample. Observations were used as techniques and observation manuals as tools to obtain data previously validated by expert judgments. It is concluded that there is a significant relationship between the emotional intelligence of distance education teachers who work in the primary education institutions of the city of Nauta and the institutional climate in the year 2022, so that the Pearson correlation coefficient ( r) is 0.01, which is high and direct.